Evolutionary trajectory of receptor binding specificity and promiscuity of the spike protein of SARS‐CoV‐2. (26th October 2022) - Planchais, Cyril; Reyes‐Ruiz, Alejandra; Lacombe, Robin; Zarantonello, Alessandra; Lecerf, Maxime; Revel, Margot; Roumenina, Lubka T.; Atanasov, Boris P.; Mouquet, Hugo; Dimitrov, Jordan D.
Abstract: SARS‐CoV‐2 infects cells by attachment to its receptor—the angiotensin converting enzyme 2 (ACE2). Regardless of the wealth of structural data, little is known about the physicochemical mechanism of interactions of the viral spike (S) protein with ACE2 and how this mechanism has evolved during the pandemic. Here, we applied experimental and computational approaches to characterize the molecular interaction of S proteins from SARS‐CoV‐2 variants of concern (VOC). Data on kinetics, activation‐, and equilibrium thermodynamics of binding of the receptor binding domain (RBD) from VOC with ACE2 as well as data from computational protein electrostatics revealed a profound remodeling of the physicochemical characteristics of the interaction during the evolution. Thus, as compared to RBDs from Wuhan strain and other VOC, Omicron RBD presented as a unique protein in terms of conformational dynamics and types of non‐covalent forces driving the complex formation with ACE2. Viral evolution resulted in a restriction of the RBD structural dynamics, and a shift to a major role of polar forces for ACE2 binding. Further, we investigated how the reshaping of the physicochemical characteristics of interaction affects the binding specificity of S proteins. Data from various binding assays revealed that SARS‐CoV‐2 Wuhan and Omicron RBDs manifest capacity for promiscuous recognition of unrelated human proteins, but they harbor distinct reactivity patterns. These findings might contribute for mechanistic understanding of the viral tropism and capacity to evade immune responses during evolution.